Clinical characteristics and risk factors for community-acquired Clostridium difficile infection: A retrospective, case-control study in a tertiary care hospital in Japan. Issue 12 (December 2015) - Mori, Nobuaki; Aoki, Yasuko
Abstract: The epidemiology of Clostridium difficile infection (CDI) has changed in the past decade. The incidence, prevalence, and severity of community-acquired CDI (CA-CDI) have increased. However, the epidemiology of CA-CDI in Japan has not been investigated. To evaluate the clinical characteristics and risk factors for CA-CDI in Japan, we conducted a retrospective, case-control study of CA-CDI at the National Hospital Organization Tokyo Medical Center between January 2010 and December 2014. Two age- and sex-matched C. difficile toxin- and culture-negative controls were assigned for each case. A total of 26 patients were identified with CA-CDI were identified. The incidence rate for CA-CDI was 1.4 per 100, 000 patient-years. Of the CA-CDI patients, 6 (23.1%) had no underlying comorbidity, 22 (84.6%) had prior exposure to antimicrobials, and 5 (19.2%) had prior exposure to antacids. Although 5 patients (19.2%) required hospitalization, none required intensive care or died. Recurrence was observed in 1 patient (3.8%). Patients with CA-CDI cases were more likely to have been recently exposed to antimicrobials compared to controls (odds ratio [OR]: 8.12, 95% confidence interval [CI]: 2.43–26.98). However, exposure to antacids was not associated with CA-CDI (OR: 0.59, 95% CI: 0.19–1.85). Our findings indicate that the incidence rate for CA-CDI in Japan is relatively low compared to the US and Europe, and that CA-CDI is usually not severe. Previous antimicrobial exposure was the main risk factor for CA-CDI, suggesting that clinicians should consider CDI in patients presenting with diarrhea who have recently received antimicrobials.